Aportes de la cultura visual para la enseñanza de las artes visuales en los estudiantes de cuarto de secundaria de una institución pública en 2022 - Chávez Sermeño, Guillermo Arturo (2024)
Images are beginning to proliferate through visual devices within society, since they are transmitted daily in people’s daily lives. Young schoolchildren are no exception, since a large number have the facility to reproduce, produce and consume the visual content that is transmitted through these media. However, this interaction could influence the construction of identity and the perception of the real world of the youngest, because these visual representations are accompanied by stereotypes, ideologies, gender roles, among others. Faced with this context, the school must pay attention to this current event. In this sense, the visual arts, which studies the analysis of artistic images, could focus on the critical analysis of the images currently transmitted by the visual media in order to broaden their perspective towards this event. Finally, this research aims to describe the contributions of visual culture to the development of the visual arts teaching strategy and critical thinking. Said investigation will be carried out in a hall of the public school, where they will analyze the works of nine students who will be chosen according to their technical abilities in order to include different interpretations.